2014
DOI: 10.1002/anie.201309503
|View full text |Cite
|
Sign up to set email alerts
|

Lanthanide‐Doped LiLuF4 Upconversion Nanoprobes for the Detection of Disease Biomarkers

Abstract: Lanthanide-doped upconversion nanoparticles (UCNPs) have shown great promise in bioapplications. Exploring new host materials to realize efficient upconversion luminescence (UCL) output is a goal of general concern. Herein, we develop a unique strategy for the synthesis of novel LiLuF4 :Ln(3+) core/shell UCNPs with typically high absolute upconversion quantum yields of 5.0 % and 7.6 % for Er(3+) and Tm(3+) , respectively. Based on our customized UCL biodetection system, we demonstrate for the first time the ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
220
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 408 publications
(225 citation statements)
references
References 37 publications
3
220
0
2
Order By: Relevance
“…With known isoelectric points, the ζ potentials of the NPs and the conjugating biomolecules can be readily tuned in opposite charges by adjusting the pH value of the reaction buffers, which allows for direct bioconjugation of the NPs via electrostatic attraction [100]. For example, by utilizing the positively charged Ln 3+ ions exposed on ligand-free LiLuF 4 :Yb, Er UCNPs, we have succeeded in the avidin functionalization of the UCNPs through electrostatic interaction [62]. Likewise, Lu and coworkers [101] developed an exceptionally simple strategy for the direct synthesis of DNA-func- -Benzotriazole-N,N,N',N'-tetramethyluronium-hexafluoro-phosphate (HBTU) and N,N-diisopropylethy (DIEA) as cross-linking reagents [65,102].…”
Section: Bioconjugationmentioning
confidence: 99%
See 3 more Smart Citations
“…With known isoelectric points, the ζ potentials of the NPs and the conjugating biomolecules can be readily tuned in opposite charges by adjusting the pH value of the reaction buffers, which allows for direct bioconjugation of the NPs via electrostatic attraction [100]. For example, by utilizing the positively charged Ln 3+ ions exposed on ligand-free LiLuF 4 :Yb, Er UCNPs, we have succeeded in the avidin functionalization of the UCNPs through electrostatic interaction [62]. Likewise, Lu and coworkers [101] developed an exceptionally simple strategy for the direct synthesis of DNA-func- -Benzotriazole-N,N,N',N'-tetramethyluronium-hexafluoro-phosphate (HBTU) and N,N-diisopropylethy (DIEA) as cross-linking reagents [65,102].…”
Section: Bioconjugationmentioning
confidence: 99%
“…SLBL method, we further designed a unique strategy for the synthesis of multi-shell LiLuF 4 : Ln 3+ @LiLuF 4 upconversion (UC) NPs via thermal decomposition (Figs 2f-i) [62]. It was observed that the overall UCL intensity was remarkably enhanced upon successive shell passivation.…”
Section: Science China Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of the mechanism of luminescence, luminescence of Ln3+ ions can be divided into down-conversion and up-conversion emission processes. The down-conversion process is the conversion of higher-energy photons into lower-energy photons [2], which often requires two main components, an inorganic matrix (known as the host) and activated Ln3+ doping ions (activators). Hitherto, many types of inorganic compounds, such as oxides, fluorides, phosphates, and vanadates, have been widely used as host materials.…”
Section: Introductionmentioning
confidence: 99%